The WINDOW IMPRESSION TECHNIQUE FOR FABRICATION OF FULL DENTURES IN PATIENT WITH FLABBY TISSUE - Muhammad Adinugraha, Irham; Patria Nawawi, Azkya; Widi Firmansyah, Sam (Journal of Health and Dental Sciences, 2024)
Fabrication of completely edentulous patients with flabby tissue can lead to the difficulty to make the impression due to the differences in compressibility of the flabby tissue and the other soft tissue. The flabby tissue can be compressed due to the pressure especially while impression making and it can lead to inaccurate impression. Fabrication of full dentures with inaccurate impression will lead to failure in providing adaptation, retention, and stabilization to the denture. The objective of this paper is to use window impression technique for patient with flabby tissue ridge. Male patient came to RSGM FKG UNJANI with major concerns of completely edentulous ridge. Patient have bad experience with full dentures because of pain while usage of the dentures, especially in anterior maxilla and never use the denture. There is no history of medical or systemic condition and patient want to make a new denture. On intraoral examination, an area of flabby tissue was observed in the anterior maxilla ridge. The patient was then planned for a full denture fabrication with window impression technique for his anterior maxilla flabby tissue. Window impression technique was able to prevent pressure while impression making and providing a well-fitted denture DOI : 10.54052/jhds.v4n2.p181-190